Analysis of Human Genetics and Related Biological Sciences in the Curriculum of Kurume University School of Medicine - YOSHINO, Makoto (Igaku Kyoiku / Medical Education (Japan), 1990)
The undergraduate curriculum of Kurume University School of Medicine was analyzed in order to know whether or not this curriculum provides essential knowledge of human genetics and related biological sciences, and whether or not it meets the need for knowledge in the rapidly developing aspects of human genetics. The total number of the lecture hours on human genetics at this medical school was found to be over three times higher than the mean number of lecture hours used in other medical schools in Japan and North America. In terms of lecture hours, molecular genetics was the predominant component, followed by population genetics. Most of the subjects in human genetics which have been generally accepted as “ compulsory” were included in various individual disciplines. However, some of the subjects, including linkage analysis and pharmacogenetics, were not mentioned in any of the lecture. These results revealed that the present curriculum provides at least core knowledge of human genetics, and that teaching of information in rapidly developing domains, such as molecular genetics, was acceptable. It is expected, however, to take some measures to assist students to integrate the components of human genetics, which are taught independently in each discipline at present, into a harmonious whole.